2012
DOI: 10.1177/1545968312461718
|View full text |Cite
|
Sign up to set email alerts
|

Functional Brain Changes Following Cognitive and Motor Skills Training

Abstract: These data suggest that altered engagement of large-scale, spatially distributed cortical brain networks and subcortical striatal brain regions may serve as candidate neural markers of training interventions. The development of reliable metrics based on activity and functional connectivity among large-scale brain networks may prove fruitful in identifying interactions between domain-general and -specific changes in brain activity that affect behavioral outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 73 publications
(39 reference statements)
3
70
0
Order By: Relevance
“…While models we discussed here exist to explain the general distinction between novel and well-practiced tasks, there is a gap in this literature in understanding how this shift occurs. Although these changes may be obscured in traditional analysis (Kelly & Garavan, 2005;Patel et al, 2013;Poldrack, 2000) there is evidence that, even over the course of an initial pre-training scan, changes in neural activation attributable to learning the stimuli can be found (Petersen et al, 1998). Our approach offers an alternative for both identifying when shifts in cognitive processing occur and also for building hypotheses concerning the expected impact cognitive changes have on neural activation.…”
Section: Models Of Practice and The Brainmentioning
confidence: 89%
See 3 more Smart Citations
“…While models we discussed here exist to explain the general distinction between novel and well-practiced tasks, there is a gap in this literature in understanding how this shift occurs. Although these changes may be obscured in traditional analysis (Kelly & Garavan, 2005;Patel et al, 2013;Poldrack, 2000) there is evidence that, even over the course of an initial pre-training scan, changes in neural activation attributable to learning the stimuli can be found (Petersen et al, 1998). Our approach offers an alternative for both identifying when shifts in cognitive processing occur and also for building hypotheses concerning the expected impact cognitive changes have on neural activation.…”
Section: Models Of Practice and The Brainmentioning
confidence: 89%
“…Much of the prior work exploring the impact of practice on neural activation forgoes an exploration of the continuous changes associated with practice in favor of pre-and post-training contrasts (for reviews: Kelly & Garavan, 2005;Patel et al, 2013). While models we discussed here exist to explain the general distinction between novel and well-practiced tasks, there is a gap in this literature in understanding how this shift occurs.…”
Section: Models Of Practice and The Brainmentioning
confidence: 93%
See 2 more Smart Citations
“…Yet, more recent research has provided evidence that these two domains are more interrelated than previously thought. A number of studies have provided evidence for links between motor and cognitive brain regions through neuroimaging or neuroanatomical studies [1,2]. It has also been shown that both motor and cognitive areas of the brain are co-activated during the performance of motor or cognitive tasks [1].…”
Section: Introductionmentioning
confidence: 99%